The third places the physical and social features influencing place attachment to universities - Tan, Armel Cizarre P. (2016)
This study was an exploration of the physical and social characteristics that encourage gathering behavior in the universities in Davao City, in the context of literature suggesting social gathering places as a contributing factor to the social capital enhancing a university community . Gathering places enhancing a community in this manner have been called third places. In that context, the third places contribution to feelings of attachment to university community was examined as well. The study was qualitative in nature and included the techniques of visual documentation, observation and survey. Photographs were taken of universities, and inventories were made of significant architectural features. Surveys were distributed to 100 student s for each university to reveal attitude toward the physical and social aspects of the third places as well as their feelings regarding the community in which they live. The data was coded and divided into four categories: physical features, social features, activities and attractiveness. The key findings regarding the physical characteristics included patron?s top five design considerations in the ideal third place. These characteristics, presented in order of preference included: Cleanliness, Comfortable Furniture, Pleasant Aroma, Views to Outside and Adequate Lighting. Other themes emerged related to people, their activities, and their feelings and attitudes regarding the third place. Each university was found to have its own unique social climate or features and culture related to sense of belonging, territoriality and ownership, productivity and personal growth, opportunity for socialization, support and networking, and sense of community. The results of the study are then applied to formulate design guidelines for a fully functioning third place. An existing student center in University of the Philippines Mindanao was redesigned and envisioned according to the design guidelines formulated.